Selective oxidation of aromatic primary alcohols to aldehydes using molybdenum acetylide oxo-peroxo complex as catalyst - Biradar, Ankush V.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Tetrahedron Letters, 2009)
Selective oxidation of various aromatic alcohols to aldehydes has been carried out with very high conversion (90%) and selectivity (90%) for aldehydes using cyclopentadienyl molybdenum acetylide complex, CpMo(CO)(3)(C CPh) (1) as catalyst and hydrogen peroxide as environmentally benign oxidant, Water-soluble Mo acetylide oxo-peroxo species is formed in situ after reaction of I with aqueous hydrogen peroxide during the Course of reaction as catalytically active species. Interestingly even though the catalyst is homogeneous it Could be recycled very easily by separating the products in organic phase and catalyst in aqueous phase using separating funnel. Even after five recycles no appreciable loss in alcohol conversion and aldehyde selectivity was observed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Homogenous catalyst; Hydrogen peroxide; Molybdenum complex; Oxidation; Oxo-peroxo; Primary aromatic alcohol